2011
DOI: 10.4161/cc.10.10.15672
|View full text |Cite
|
Sign up to set email alerts
|

Aquaglyceroporins serve as metabolic gateways in adiposity and insulin resistance control

Abstract: Aquaglyceroporins (AQP3, AQP7, AQP9 and AQP10) encompass a subfamily of aquaporins that allow the movement of water and other small solutes, especially glycerol, through cell membranes. Adipose tissue constitutes a major source of glycerol via AQP7. We have recently reported that, in addition to the well-known expression of AQP7 in adipose tissue, AQP3 and AQP9 are also expressed in omental and subcutaneous fat depots. Moreover, insulin and leptin act as regulators of aquaglyceroporins through the PI3K/Akt/mTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
3
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 83 publications
6
112
3
6
Order By: Relevance
“…Evidence for negative feedback regulation in lipolytic states to restrict glycerol release from fat cells by restricting AQP7 expression comes from treatment of cells with leptin, isoprenaline and carboxymethyl chitin (Rodriguez et al, 2011a). It is also thought that insulin regulates AQP7 levels, but the evidence is contradictory and there may be divergent effects of insulin on the regulation of all aquaglyceroporins in humans compared to rodents (Kishida et al, 2001, Rodriguez et al, 2011b.…”
Section: Phosphatidylinositol 3-kinasementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for negative feedback regulation in lipolytic states to restrict glycerol release from fat cells by restricting AQP7 expression comes from treatment of cells with leptin, isoprenaline and carboxymethyl chitin (Rodriguez et al, 2011a). It is also thought that insulin regulates AQP7 levels, but the evidence is contradictory and there may be divergent effects of insulin on the regulation of all aquaglyceroporins in humans compared to rodents (Kishida et al, 2001, Rodriguez et al, 2011b.…”
Section: Phosphatidylinositol 3-kinasementioning
confidence: 99%
“…The aquaglyceroporin, AQP7, is responsible (with AQP3) for the majority of glycerol transport across the membranes of adipose tissue (Rodriguez et al, 2011a) and signalling pathways, including phosphatidylinositol 3-kinase, have been associated with the regulation of aquaglyceroporin transcription (Kishida et al, 2001). Evidence for negative feedback regulation in lipolytic states to restrict glycerol release from fat cells by restricting AQP7 expression comes from treatment of cells with leptin, isoprenaline and carboxymethyl chitin (Rodriguez et al, 2011a).…”
Section: Phosphatidylinositol 3-kinasementioning
confidence: 99%
“…Knocking out AQP7 leads to obesity (22) and insulin resistance (39,54). As to the potential role of the NH 3 permeability of AQP7, it is well known that intense exercise can lead to increases of [NH 3 ] in the arterial plasma that may approach levels toxic to the brain (2) if not opposed.…”
Section: Functional Analysis Of Aqp0 -9mentioning
confidence: 99%
“…It was recently suggested that AQP3 and AQP9 represent additional pathways for transport of glycerol in human adipocytes and that these AQPs are therefore potentially responsible for AQP7 redundancy. 22 Here we present the cases of three children from unrelated families. All three children had psychomotor retardation of unknown etiology, pronounced renal glycerol loss (hyperglyceroluria), and a subclinical, platelet-dense granule secretion defect.…”
Section: Introductionmentioning
confidence: 99%